A taxonomy of pedestrian evacuation infrastructure for urban areas; an assessment of resilience towards natural hazards. Issue 2 (1st November 2022) - Fathianpour, Azin; Jelodar, Mostafa Babaeian; Wilkinson, Suzanne; Evans, Barry
Abstract: Many people in the world live in hazardous environments and are susceptible to disasters. In the time of a destructive event, a resilient community must be prepared to mitigate the event and quickly respond. An effective mitigation plan can lead to fewer fatalities and damages. One of the most critical tasks for mitigation is the evacuation process. Wherein short notice time, overcrowding, bottlenecks in infrastructure and challenging terrain and topography may worsen the situation. Amongst other things, the evacuation process encompasses transportation infrastructures referred to as corridors, signs, pedestrian footpaths, and/or shelter infrastructures for keeping people safe. Evacuation infrastructure can also become damaged after the event; therefore, it's imperative to have a robust assessment of different evacuation infrastructures. This study will investigate the characteristics of the available evacuation infrastructure and outline the general drawbacks. A systematic methodology for reviewing articles has been implemented to understand how vulnerable cities can be more prepared, especially for pedestrian evacuation. An evacuation scoring system for pedestrians will be developed to investigate evacuation infrastructure in terms of different resilience features, such as redundancy, safe to fail, readiness, capacity. The most practical evacuation system will be estimated, with a final output being to provide the features of a successful pedestrian evacuation system for future policy use.